2016
DOI: 10.1016/j.jcot.2016.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological profile of sports-related knee injuries in northern India: An observational study at a tertiary care centre

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 10 publications
1
31
2
Order By: Relevance
“…Our result is similar to the result of previous studies from the USA and the UK, which demonstrated an increased incidence of these injuries with increased level of competition [27,28]. The most common mechanism led to these injuries was due to a non-contact mechanism (68.7%); this is consistent with what was observed by John et al (64.4%) of their sample [13]. Furthermore, The American Journal of Sports Medicine reported by Arendt and Dick that non-contact mechanism was the reason for most ACL injuries among college basketball and soccer players in the USA [29].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our result is similar to the result of previous studies from the USA and the UK, which demonstrated an increased incidence of these injuries with increased level of competition [27,28]. The most common mechanism led to these injuries was due to a non-contact mechanism (68.7%); this is consistent with what was observed by John et al (64.4%) of their sample [13]. Furthermore, The American Journal of Sports Medicine reported by Arendt and Dick that non-contact mechanism was the reason for most ACL injuries among college basketball and soccer players in the USA [29].…”
Section: Discussionsupporting
confidence: 92%
“…At King Fahd University Hospital, Al Khobar, Eastern Province, Saudi Arabia, a prospective study of sportsrelated injuries was conducted in a period of 12 months and knee injuries represented the majority of injuries encountered with a 27% [12]. Soccer is the leading sport activity associated with knee injuries [12,13]. In the USA, most of the collegiate studies were concerned with knee injuries among athletes; such an epidemiological study was conducted in the National Collegiate Athletic Association (NCAA) among men's and women's volleyball athletes where the knee joint was the most commonly injured body part (25.5% in males; 16.3% in females), with different patterns of injuries between male and female [14].…”
Section: Introductionmentioning
confidence: 99%
“…Anterior cruciate ligament (ACL) tear is one of the most common ligament injuries of the knee 1,2 . The etiology of ACL tear has been proven to be multifactorial 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…Rupture of the anterior cruciate ligament (ACL) is a common sports injury, and is especially associated with jump-landing tasks and side-step cutting activities such as basketball, soccer or tennis [1][2][3] . Despite the successes of ACL reconstruction surgery, up to 90% of patients continue to develop early osteoarthritis within 20-years post-surgery 4 .…”
Section: Introductionmentioning
confidence: 99%
“…This is an alarmingly high number given that patients with ACL injuries are often young athletes or adults who are fit and healthy. Interestingly, a high percentage of ACL ruptures occurs in non-contact situations, indicating that ACL injuries are likely influenced by poor neuromuscular control and improper movement execution rather than an external impact force delivered directly to the knee joint [1][2][3] . In general, female athletes seem to exhibit a greater incidence of non-contact ACL injury compared to male counterparts, which has been associated with the females' reduced capability to stabilise the joint during high-impact movements 5 .…”
Section: Introductionmentioning
confidence: 99%